TREN PENGEMBANGAN KAJIAN ILMU FALAK DI PONDOK PESANTREN AL-ISLAM JORESAN MLARAK PONOROGO - Muhtar, Imroatul Munfaridah (UIN ALAUDDIN MAKASSAR, 2022)
Astronomy is a unique and rare science that is considered to provide real benefits to Muslim society. One of the Islamic Boarding Schools in Ponorogo which preserves astronomy by incorporating this knowledge into a formal curriculum that combines astronomy to observe the new moon. This research is a qualitative descriptive research with data collection techniques using observation, interviews and documentation then the analysis uses development theory and astronomy theory which aims to find out the methods of studying astronomy at Al-Islam Islamic Boarding School Mlarak Ponorogo and to find out the implications of the development of studying astronomy on students and the community around Joresan Mlarak Ponorogo Al-Islam Islamic Boarding School. The results of this study were found in learning using 2 methods, namely classical and contemporary in which the classical method with reference to the book of Sulam al-Nayiro is given to MAK majors in grades 5 and 6 with material from the beginning of the moon to eclipses, while in class 4 the MAK majors students get learning astronomy with contemporary methods using ephemeris with initial materials prayer time and Qibla direction. So that the implications of studying astronomy are able to change students to be interested in information related to determining the beginning of the Hijri month, solar eclipses and lunar eclipses.